2021
DOI: 10.3390/cells10030690
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein Inhibitor Tariquidar Plays an Important Regulatory Role in Pigmentation in Larval Zebrafish

Abstract: Zebrafish has emerged as a powerful model in studies dealing with pigment development and pathobiology of pigment diseases. Due to its conserved pigment pattern with established genetic background, the zebrafish is used for screening of active compounds influencing melanophore, iridophore, and xanthophore development and differentiation. In our study, zebrafish embryos and larvae were used to investigate the influence of third-generation noncompetitive P-glycoprotein inhibitor, tariquidar (TQR), on pigmentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Pigmentation in the eyes and dorsal regions was lighter and displayed a spotted distribution pattern, as opposed to the darker, uniformly distributed pigment observed in the control group. Typically, zebrafish embryos are cultured in a medium containing PTU, a highly effective sulfur-based TYR inhibitor, to inhibit melanin production [43]. Our findings indicated that both TFMH and T-6 significantly reduced melanin content and TYR activity in zebrafish, with their inhibitory effects intensifying with increasing concentrations.…”
Section: Discussionmentioning
confidence: 77%
“…Pigmentation in the eyes and dorsal regions was lighter and displayed a spotted distribution pattern, as opposed to the darker, uniformly distributed pigment observed in the control group. Typically, zebrafish embryos are cultured in a medium containing PTU, a highly effective sulfur-based TYR inhibitor, to inhibit melanin production [43]. Our findings indicated that both TFMH and T-6 significantly reduced melanin content and TYR activity in zebrafish, with their inhibitory effects intensifying with increasing concentrations.…”
Section: Discussionmentioning
confidence: 77%
“…Zebrafish share a genetic similarity of 87% with humans, and their melanin synthesis mechanism closely resembles that of humans. , The genes involved in melanocyte regulation in zebrafish are well conserved with those in humans. , Additionally, the transparent skin of zebrafish embryos and larvae allows for convenient in vivo imaging and monitoring of melanin changes, making zebrafish an ideal model for studying melanocyte development and pigmentary disorders. Wild-type (AB) zebrafish (6 hpf) were used to evaluate the minimal toxic concentration (MTC) of compounds T0 and T3 , as well as kojic acid (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…All steps of reverse transcription were assessed according to the manufacturers’ protocols. qPCR was performed using SYBR Green (SYBR Select Master Mix, Applied Biosystems, Foster City, CA, USA) on a 7500 Fast Real-Time PCR System instrument (Applied Biosystems, Foster City, CA, USA) under previously described conditions [ 14 ]. Oligonucleotide primers were selected to detect: vascular endothelial growth factor Aa ( vegfaa ), vascular endothelial growth factor receptor 1 ( vegfr1 ), vascular endothelial growth factor receptor 2 ( vegfr2 ), placental growth factor a ( pgfa ), placental growth factor b ( pgfb ), fibroblast growth factor 2 ( fgf2 ), transforming growth factor-beta 1 ( tgfb1 ), insulin growth factor 2a ( igf2a ) and insulin growth factor 2b ( igf2b ).…”
Section: Methodsmentioning
confidence: 99%